2014
DOI: 10.1097/01.sa.0000441004.73409.91
|View full text |Cite
|
Sign up to set email alerts
|

Protective Mechanical Ventilation During General Anesthesia for Open Abdominal Surgery Improves Postoperative Pulmonary Function

Abstract: Background: The impact of intraoperative ventilation on postoperative pulmonary complications is not defined. The authors aimed at determining the effectiveness of protective mechanical ventilation during open abdominal surgery on a modified Clinical Pulmonary Infection Score as primary outcome and postoperative pulmonary function. Methods: Prospective randomized, open-label, clinical trial performed in 56 patients scheduled to undergo elective open abdominal surgery lasting more than 2 h. Patients were assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
190
3
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(211 citation statements)
references
References 27 publications
5
190
3
13
Order By: Relevance
“…However, these studies demonstrated that this mode of ventilation is feasible in open abdominal surgery with no adverse eff ects [23], [25]. In contrast to the previous studies, Severgnini et al, comparing a lung protective mechanical ventilation consisting of a V T of 7 ml/kg ideal body weight with PEEP levels of 10 cmH 2 O and recruitment maneuvers versus a V T of 9 ml/kg without PEEP, showed benefi cial eff ects of the lung-protective strategy during general anesthesia lasting more than 2 hours [26]. Th e lung-protective strategy improved postoperative respiratory function in terms of dynamic spirometry, oxygenation, and pulmonary complications for up to 5 days after surgery, without increasing the incidence of intraoperative complications.…”
Section: Abdominal Surgerycontrasting
confidence: 39%
See 2 more Smart Citations
“…However, these studies demonstrated that this mode of ventilation is feasible in open abdominal surgery with no adverse eff ects [23], [25]. In contrast to the previous studies, Severgnini et al, comparing a lung protective mechanical ventilation consisting of a V T of 7 ml/kg ideal body weight with PEEP levels of 10 cmH 2 O and recruitment maneuvers versus a V T of 9 ml/kg without PEEP, showed benefi cial eff ects of the lung-protective strategy during general anesthesia lasting more than 2 hours [26]. Th e lung-protective strategy improved postoperative respiratory function in terms of dynamic spirometry, oxygenation, and pulmonary complications for up to 5 days after surgery, without increasing the incidence of intraoperative complications.…”
Section: Abdominal Surgerycontrasting
confidence: 39%
“…Th e lung-protective strategy improved postoperative respiratory function in terms of dynamic spirometry, oxygenation, and pulmonary complications for up to 5 days after surgery, without increasing the incidence of intraoperative complications. Although there was no signifi cant diff erence in the hospital length of stay between groups, 20 % of the patients in the lungprotective group, compared with 40 % in the control group, were still in hospital on postoperative day 14 [26]. A recent multicenter randomized clinical trial in which lung-protective ventilation with a V T of 6-8 ml/kg predicted body weight, PEEP 6-8 cmH 2 O and recruitment maneuvers repeated every 30 minutes was compared with non-protective ventilation with V T 10-12 ml/kg without PEEP, found that the lung-protective ventilation signifi cantly reduced major pulmonary and extrapulmonary complications from 27.5 % to 10.5 % [27].…”
Section: Abdominal Surgerymentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies suggest intraoperative ventilation settings affect postoperative pulmonary outcomes 1,[9][10][11][12][13] . Many surgical patients undergo short-term ventilation with large V T (greater than 10 mL/kg predicted body weight [PBW]) 12,14 without negative consequences.…”
Section: Introductionmentioning
confidence: 99%
“…They found that using lower tidal volume, PEEP, and recruitment maneuvers resulted in significantly improved pulmonary function test results up to 5 days after surgery, fewer chest x-ray findings, and improved Clinical Pulmonary Infection Score. 22 These findings need to be replicated in a larger group of patients, but present unique options for preventing PPCs. Very recently, Futier et al demonstrated that the use of PEEP, recruitment, and low tidal volume during open abdominal surgery resulted in fewer PPCs, compared to tidal volume of 10 -12 mL/kg and no PEEP.…”
Section: Intraoperative Mechanical Ventilationmentioning
confidence: 99%